2002
DOI: 10.1086/339225
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationships among Gender, Marital Status, and Mental Health

Abstract: Three decades ago, Grove introduced his sex-role theory of mental illness, which attributes women's higher rates of psychological distress to their roles in society. Central to his hypothesis is that marriage is emotionally advantageous for men and disadvantageous for women. This article revisits this topic with data from the National Survey of Families and Households. The analyses indicate that the emotional benefits of marriage apply equally to men and women, but that men and women respond to marital transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

56
541
12
30

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 619 publications
(639 citation statements)
references
References 57 publications
56
541
12
30
Order By: Relevance
“…This conflicts with the literature that has generally found that being married has a unique protective effect on individuals through the regulation of risky behaviours and cautionary attitudes towards potential dangers (Kim & McKenry, 2002;Simon, 2002;Umberson, 1992). It may, however, be the case that the processes governing safe water, specifically, are different than other health-related issues.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 75%
See 1 more Smart Citation
“…This conflicts with the literature that has generally found that being married has a unique protective effect on individuals through the regulation of risky behaviours and cautionary attitudes towards potential dangers (Kim & McKenry, 2002;Simon, 2002;Umberson, 1992). It may, however, be the case that the processes governing safe water, specifically, are different than other health-related issues.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 75%
“…The state of being married, relative to individuals who are single, widowed, separated, or divorced, has been found to have a protective effect on individuals, for a number of reasons, including economic efficiency, orderliness, regulation of risky behaviours, and emotional social support (Kim & McKenry, 2002;Simon, 2002;Umberson, 1992). It would, therefore, be expected that a skeptical and more cautionary attitude towards safe drinking water in the home would be observed by married respondents.…”
Section: Variables and Hypothesesmentioning
confidence: 99%
“…However, the existing longitudinal studies indicate, like the cross-sectional studies, that marriage is associated with higher life satisfaction (39,43) and greater affective happiness (44). Evidence moreover suggests that marriage is associated with better mental health, physical health, and longevity, even controlling for baseline health (45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55). Concerning character and virtue, although understudied and current outcome measures are inadequate, there is longitudinal evidence that marriage is associated with higher level of personal growth (44), and with a reduction in crime for those at high risk (56).…”
Section: Prominent Pathways To Human Flourishingmentioning
confidence: 99%
“…This article turns out to be about individuals who have no children younger than age 18 living in the home. A similar problem is encountered in reports based on survey research, where parenthood is often defined as having children living at home (e.g., Arber & Cooper, 2000;Evandrou & Glaser, 2004;McLanahan & Adams, 1987;Simon, 2002), so that empty nesters and childless individuals are grouped together. A few years ago, one of us was a discussant in a session during a national meeting of family researchers.…”
Section: What Is a Child?mentioning
confidence: 91%
“…Already in Durkheim's (1896Durkheim's ( /1951) study of suicide, this was a potential problem of interpretation. In 20th-century discussions of the link between marital status and well-being, this issue has repeatedly been revisited (Gove, 1984;Gove, Style, & Hughes, 1990;Mastekaasa, 1992;Simon, 2002); however, studies of childlessness have, for the most part, ignored it. Two researchers recently stated, "To our knowledge, prior research has not examined the simultaneous contextualizing influences of sex and marital status on the effects of childlessness for elderly persons psychological wellbeing" (Zhang & Hayward, 2001, p. S313).…”
Section: Childlessness and Life Contextmentioning
confidence: 99%